Geopolitical Interests of the United States of America in the Central Asian Republics - ASKERBEK, Assel; YESDAULETOVA, Ardak; YESDAULETOV, Aitmukhanbet; ALPEISSOV, Amirzhan; ADILBEKOV, Sagdat (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019, 2019)
The article is devoted to the policy of the United States of America in Central Asian region. The focus of the article is centered on the US interests as geopolitical imperatives aimed at fighting for the spheres of influence with important factors such as the Russian Federation and the People's Republic of China. The method of system analysis and historical and chronological study of the issue revealed that the United States passed through several periods in the development of its policy in the region. In light of the aggravation of relations between the two sides, as well as the trade war between the US and China, the countries of the region are experiencing geopolitical impact and economic difficulties that make them become ‘closer’ to the United States of America.